FAITH AMID EMPLOYMENT ANXIETY: A CONTEXTUAL-SOCIOLOGICAL THEOLOGICAL ANALYSIS OF THE JOB HUGGING PHENOMENON IN INDONESIA - Mulia Wongdi; Yanto Paulus Hermanto (STT Bethel Indonesia Jakarta, 2026)
The phenomenon of job-hugging has emerged increasingly in the modern workplace as a response to post-pandemic economic uncertainty. To date, however, it has predominantly been examined through economic and psychological frameworks. This study explores job hugging from a theological perspective by analyzing the relationship between faith and anxiety in the context of contemporary working life in Indonesia. This research employs a contextual, systematic, theological approach using a qualitative, reflective method grounded in a review of theological literature, the theology of work, and contemporary pastoral theology. The findings indicate that job-hugging does not merely reflect a survival strategy but also reveals a crisis of modern faith, namely, the displacement of ultimate security from divine providence to employment and worldly stability. Anxiety is understood both as a spiritual symptom of weakened faith and as a reflective space that may lead to a deepening of existential faith. The novelty of this study lies in its interpretation of job hugging as a theological phenomenon that manifests the dialectical dynamic between faith and anxiety, as well as in its formulation of pastoral implications that situate work as vocation within the framework of providentia Dei. This study affirms the contribution of systematic theology in enriching contemporary discourse on the modern world of work and in strengthening the pastoral accompaniment of believers.